Experimental investigation of water-rock reaction for the reinjection of sandstone geothermal reservoirs: A case from Neogene Guantao Formation in Tianjin. (July 2023) - Guo, Yanlong; Xu, Yishuo; Wang, Huajun; Shen, Jian; Zhao, Sumin
Abstract: Reinjection is of importance to ensure the sustainable utilization of geothermal resources. However, there are still challenges for achieving complete reinjection of pore-type sandstone reservoirs. Taking Neogene sandstone in Tianjin as an example, water-rock reaction experiments under four reinjection fluids at 60 °C and 15 MPa were designed and performed. From the point of view of inner pores and permeability, the variations of pH, TDS and mineral compositions were compared, and their influences on the reinjection were analyzed. Responses of hydrogen and oxygen isotopes to water-rock reactions were obtained. Further, the statistical method including principal component analysis, cluster analysis and Pearson relevance analysis revealed the intrinsic correlations among 9 major hydrochemical compositions, 41 trace elements and 6 mineral compositions during the water-rock reactions. Test results showed that nanofiltration treatment water had more advantages as an alternative reinjection fluid, and the municipal tap water was not recommended. It was found that specific trace elements (e.g. Cu, Pb, Ni, Co, Rb) can be used as potential indicators of dissolution or precipitation of sandstone minerals (e.g. quartz, calcite, ankerite, clay minerals). The present results can provide helpful references for optimal selection of reinjection fluids as well as monitoring and evaluation of geothermal reservoirs.